Phonetic Motivation in 200 years era - شهلا شریفی; لیلا عرفانیان قونسولی (مطالعات زبانی و بلاغی)
phonetic motivation is what we can guess the meaning via sound. Some people believe that primary words were more iconic and by passage of time, because of phonetic changes and â¦ the motivation has been reduced. In this research, for studying this thesis, four passages with outline of a journey from present time have been considered and 2800 content words from it have been extracted. Then phonetic motivation in these words has been considered. Afterwards, the results of these passages have been compared with results from considering 2800words of passages from200years before in order to answer this question that from past 200years, Persian language has been more motivated or vice versa. Comparison of the results of two time courses didnât show a meaningful change in the number of words with phonetic motivation and semi phonetic motivation in the present time in comparison with 200 years before. Therefore, it may be claimed that since 200 years before until now, no change has happened in the phonetic motivation of Persian words.